POTENSI PAJAK TINGKAT HUNIAN KAMAR HOTEL PADA 5 (LIMA) KABUPATEN/KOTA DI PROVINSI KALIMANTAN BARAT - B21108035, LITA PUJIASTUTI (Jurnal Pembangunan dan Pemerataan, 2015)
This study, entitled "Potential Tax Hotel Room Occupancy Rate at 5 (five) Regency / City in West Kalimantan Province" aims to to find out great potential hotel tax that is actually owned by the Province of West Kalimantan. The study was conducted using data from 2002-2011 by taking a sample which is 5 (five) Regency / City in West Kalimantan. This research using a descriptive methode. To calculate the potential its using several related variables, such as the number of rooms, number of hotel, average room rates and room rates were determined magnitude. The results showed that the potency Taxes on five (5) districts / cities in West Kalimantan is quite large, far above the value of the previous hotel tax revenue. Hotel tax potential in five (5) districts / cities in West Kalimantan in 2014 amounted to Rp 20.836.303.391,- while the realization in 2013 only amounted to Rp 15.681.865.074, -. Â  Keywords: Hotel Tax, Hotel Tax Potential, Tax Revenue Hotel, Hotel Room Occupancy Rate